PENGARUH VOLATILITAS PENJUALAN, SIKLUS OPERASI, TINGKAT UTANG DAN BOOK TAX DIFFERENCES TERHADAP PERSISTENSI LABA - Rifda Luthfiana (2022)
This study aims to examine and analyze the influence of sales volatility, operating cycle, debt level and book tax differences on earnings persistence in manufacturing companies listed on the Indonesia Stock Exchange (IDX) period 2017-2019. The sample in this study was selected through a purposive sampling method and collected 186 data samples. The data analysis technique used is multiple linear regression of panel data, classical assumption test, and hypothesis testing with a significance level of 5% (0.05). The results of this test state that temporary book tax differences have negative effect on earnings persistence. sales volatility, operation cycle, leverage, and permanent book tax differences has no effect on earnings persistence in manufacturing companies listed in Indonesia Stock Exchange period 2017-2019. Keywords: Earnings Persistence, Sales Volatility, Operating Cycle, Leverage, Book Tax Differences.